Dyslipidemia in subclinical hypothyroidism requires assessment of small dense low density lipoprotein cholesterol (sdLDL-C) - Saric Maida Seferovic; Jurasic Miljenka-Jelena; Sovic Slavica; Kranjcec Bojana; Glivetic Tatjana; Demarin Vida (Sciendo, 2017)
Background. Usually both hypothyroidism and hyperthyroidism are related to the cardiovascular and cerebrovascular disease development. The relationship between subclinical hypothyroidism has been widely investigated but the findings remain controversial. The aim of the present study was to evaluate the lipid profile in patients with subclinical hypothyroidism (SHypo) in comparison to controls and to determine the association of SHypo and dyslipidemia in attempt to find importance of small dense low-density lipoprotein cholesterol (sdLDL-C) in atherosclerosis. Material and methods. In this study we included 100 women, aged 30 to 70 years that were divided into subgroups according to their age. According to the values of levels of thyroid hormones they were divided into euthyroid (control) group (n = 64) and (newly discovered) subclinical hypothyroidism (SHypo) group (n = 36). A high-sensitivity C-reactive protein (hs-CRP) and lipid profile, including small dense low-density lipoprotein cholesterol (sdLDL-C) were determined. Body weight and height were measured and BMI calculated. History of the current illness, medication, alcohol consumption and cigarettes smoking were noted. Results. Changed lipid profile as well as elevated triglycerides and sdLDL-C were observed in the group with subclinical hypothyroidism compared to the control group. Conclusions. It is important to determine serum lipid levels, especially serum sdLDL-C levels at an early stage of subclinical hypothyroidism, since they represent atherogenic LDL particles and are better indicators for dyslipidaemia in subclinical hypothyroidism and the development of atherosclerosis with potential complications such as cardiovascular and cerebrovascular diseases.